2017
DOI: 10.1371/journal.pone.0169352
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mediators in Tracheal Aspirates of Preterm Infants Participating in a Randomized Trial of Inhaled Nitric Oxide

Abstract: BackgroundVentilated preterm infants frequently develop bronchopulmonary dysplasia (BPD) which is associated with elevated inflammatory mediators in their tracheal aspirates (TA). In animal models of BPD, inhaled nitric oxide (iNO) has been shown to reduce lung inflammation, but data for human preterm infants is missing.MethodsWithin a European multicenter trial of NO inhalation for preterm infants to prevent BPD (EUNO), TA was collected to determine the effects of iNO on pulmonary inflammation. TA was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…During iNO treatment, routine MetHb and exhaled NO 2 monitoring are required. With low-dose iNO, the concentrations of those two substances are small and stable; their safety has been confirmed in other studies of iNO in infants [22]. Another possible side-effect of iNO is that it can inhibit platelet aggregation and adhesion to the vascular endothelium, thereby prolonging bleeding time.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…During iNO treatment, routine MetHb and exhaled NO 2 monitoring are required. With low-dose iNO, the concentrations of those two substances are small and stable; their safety has been confirmed in other studies of iNO in infants [22]. Another possible side-effect of iNO is that it can inhibit platelet aggregation and adhesion to the vascular endothelium, thereby prolonging bleeding time.…”
Section: Discussionmentioning
confidence: 81%
“…Studies in different animal models have demonstrated that iNO ameliorates lung injury by inhibiting inflammatory cytokines and oxidative damage [19][20][21]. A recent study on iNO-mediated prevention of bronchopulmonary dysplasia in Europe showed that iNO treatment may decrease several inflammatory and fibrotic factors in the lungs [22]. Preemptive iNO in human liver transplantation surgery led to clear anti-inflammatory effects in liver grafts which protected graft function, ameliorated pathological changes, and reduced postoperative morbidity [23].…”
Section: Discussionmentioning
confidence: 99%
“…These studies consistently reported an increased in the levels of ceramide in tracheal aspirates in pediatric patients undergoing mechanical ventilation [172,173]. However, ceramide production tends to increase with postnatal development and this increase shows no or even a negative correlation with long term complications [171,172].…”
Section: Ceramide and Diseasementioning
confidence: 97%
“…Baro- and volutrauma and oxygen toxicity are thought to be the main triggers [ 8 ]. Morphological changes due to oxidative stress result in the disruption of lung development [ 27 ], accompanied by increased proinflammatory cytokine and chemokine expression and immune cell infiltration in lung tissue [ 28 30 ]. Apoptosis and proliferation play an important role in normal cell turnover and tissue development.…”
Section: Introductionmentioning
confidence: 99%